(untitled) (Research, Society and Development, 2020)
With the enactment of the Constitution of 1988, many of the arbitrary determinations of Institutional Act number 5 were contrasted by the inclusion of fundamental rights within the stone clauses. In this sense, the objective of this article is to investigate the extent to which the nation’s re-democratization process was able to reward Brazilian society with regard to the historical debt caused by military intervention and the implementation of AI-5. In this perspective, the present article, through exploratory research, of qualitative nature, deductive method, collection of documental and bibliographic data, developed in order to carry out a historical investigation on the theme, reaching the result that, although the The process has been largely successful, there are still gaps in the Federal Constitution that allow rules and decrees similar to the Institutional Acts to be enacted, as well as laws that guarantee fundamental rights to be disregarded. Finally, it was concluded that there is still an urgent need to protect human rights in the Constitutional Text, since the aforementioned inconsistencies do not guarantee the full preservation of fundamental guarantees.